Drug abuse - Fradin, Dennis B. (Chicago : Childrens Press, 1988)
Defines drugs, discusses the different types and their effects on people when used or abused, and suggests ways of preventing or counteracting drug abuse.
Includes index.
13 30
Keywords: Drug abuse -- United States -- Prevention -- Juvenile literature; Drugs; Drug abuse; Drug abuse -- United States -- Juvenile literature